Manganese-Enhanced Magnetic Resonance Imaging: Application in Central Nervous System Diseases - Yang, Jun; Li, Qinqing (Frontiers in Neurology, 2020)
Manganese-enhanced magnetic resonance imaging (MEMRI) relies on the strong paramagnetism of Mn2+. Mn2+ is a calcium ion analogue and can enter the excitable cells through voltage-gated calcium channels. It can be transported along the axons of neurons via microtubule based fast axonal transport. Based on these properties, MEMRI is used to describe neuroanatomical structures, to monitor neural activity, and to evaluate axonal transport rates. The application of MEMRI in preclinical animal models of central nervous system (CNS) diseases can provide more information for the study of disease mechanisms. In this article, we provide a brief review of MEMRI use in CNS diseases from neurodegenerative diseases to brain injury and spinal cord injury.